Cross-cultural Adaptation and Psychometric Properties of the Indonesian Version of the Self-Regulation for Dental Home Care Questionnaire - Rachmawati, Yuanita L.; Loster, Jolanta E.; Maharani, Diah A.; Loster, Bartłomiej W. (UI Scholars Hub, 2018)
Few studies have reported the role of motivation in patient adherence to dental-care programmes or dental home care and prevention of oral disease, particularly in Indonesia. Objective: To cross-adapt the Self-Regulation for Dental Home Care Questionnaire (SRDHCQ) to the Indonesian version, and to study self-regulation for dental home care among adolescents. Methods: The SRDHCQ was cross culturally adapted to the Indonesian adolescents aged 12-13 years old to test its reliability and validity. Intraoral examination was conducted by a single examiner to analyse the number of decayed teeth. The SRDHCQ contains 22 questions with a 7-point scale, which comprises of integrated, identified, introjected, external regulation and amotivation domains. Respondents were randomly selected from 11 junior high schools at six districts in Jakarta. Results: Total respondents studied were 317 students, with prevalence of 71% of the students having decayed teeth, and average number decayed teeth was 2.1. The test and test-retest reliability and Cronbach’s alpha for internal consistency were 0.838 and 0.929, respectively. No significant difference was observed in total SRDHCQ scores between genders. Construct and discriminant validity analysis showed significant results. Conclusions: Our results support the reliability and validity of the Indonesian SRDHCQ for adolescents in Indonesia.